A review of permanent magnet linear motor with halbach array - Parveziqbal A.K.M.; Mokhtar F.A.M; Sahari K.S.M.; Aris I. (Medwell Journals, 2023)
Utilizing Halbach magnet array, magnetic flux can be built up on the strong side of the array while the flux cancelled on the other weak side. Inherently, rotor of rotary motor has infinite rotational length with respect to its rotation while mover of the linear motor has finite length with respect to mover's translation. This study starts with a brief introduction of Halbach array and its method in designing linear motors. It then discusses the difference between conventional permanent magnet array with Halbach array and also the difference between slotted type and slotless Halbach array. This study has reviewed the implementation of Halbach array in machines with different topologies and the Halabch magnetization field distribution. Medwell Journals, 2016.